The Relationship of Chemical Compounds and Crystal Development in Porang Tuber (Amorphophallus muelleri Blume) - Chairiyah, Nurul; Harijati, Nunung; Mastuti, Retno (The Journal of Experimental Life Science, 2023)
Chemical compounds are presumed to interact with each other and potentially affect the crystal development of porang tubers. This study focused on glucomannan and calcium oxalate (CaOx) as chemical compounds found in porang. Crystal development was analyzed by microscopic observation. The tuber tissue was used for microscopic slides and was harvested two weeks before the plants lost their leaves, when the plants lost their leaves, and two weeks after the plants lost their leaves. The CaOx and glucomannan content was measured using a modified extraction method. The increasing of CaOx content tends to increase the number of CaOx crystals. The analysis showed that the crystal density could affect the increasing of tuber weight possibility. There was a development process in raphide crystals that showed by different sizes at three harvest times, which the others were not. The results also indicated that glucomannan might influence the crystal density and the CaOx content. It can be concluded that glucomannan can potentially induce CaOx synthesis and crystal count increase. Keywords: Caox, Crystal, Development, Glucomannan, Interact, Porang.